Implementasi Teknologi Multimedia pada Akun Instagram "@petualanganmenujusesuatu" - Putra, Ridi Rahmanda; Salim, Tamara Adriani (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
Multimedia technology is a sophisticated computer technology that can process data into interesting and useful information for the community. The Instagram account of @petualanganmenujusesuatu is a content creation account that is focused on mental health awareness. In content deployment, account of @petualanganmenujusesuatu is one account that deploy content by using the elements of multimedia technology. This research will identify the use of elements of multimedia technology carried out by the @petualanganmenujusesuatu account. This research is qualitative research with a case study method which data collection is done by means of observation and interviews. The @petualanganmenujusesuatu account applies all elements of multimedia technology to distributes the content. Content about mental health is in the form of storytelling through comic strips and characters. The results of this research indicate that the @petualanganmenujusesuatu account uses all multimedia elements in every content that is distributed on its account. The elements of multimedia technology that form the basis of the content are images and some animated videos combined with text and audio.